Physicochemical and Functional Value of Lettuce: Effect of Mulching Technique Used During Production on Postharvest Storage - Gonzalez, Roxana Elizabeth; Lanza Volpe, Melisa; Soto Vargas, Verónica Carolina (MDPI, 2025)
Artículo presentado al 5th International Electronic Conference on Foods, 28–30 October 2024